Book review for Bloomsbury Press - Assis, Paulo de (2023)
This little book is not a dictionary in the accepted sense of the word – although it is nonetheless reassuring, mind you! It is an almanac. An almanac (from the Arabic المنحة al-minḥa oder المنح al manḥ, meaning ‘gift,’ or ‘present’) was some kind of early calendar, a collection of texts and hints at the positions of planets, sunrise and sundown, etc. Our almanac is ‘astronomical’ in such a way, that it presents a very personal and playful astronomy. It gives a collection of ‘sound words’ that have figured as the individual guiding-stars for the participating sound artists and scholars, guiding-stars perceived from various positions and locations on this planet. Unlike volumes announcing ‘Keywords of ….’ Or ‘Key Concepts of …,’ these heavyweights – even heavyweight champions!) that operate with all the tricks of the trade, with combinations of punches, jabs, even liver shots, this almanac follows a more humble approach, minor, an intimate tai-chi, rather. So, instead of a reassuring dictionary, with grand definitions that promise stability over time and space, here we have an unstable, personal, and playful almanac, that is reassuring not by rational argumentation, but by lived example. John Cage’s wish for mankind was ‘Happy New Ears.’ Maybe, with this almanac, we can be inspired to listening differently.
FRIS
1
Keywords: MetamusicX:Transdisciplinary Encounters in and Beyond Music